Analysis of the Influence of Competency, Work Motivation, and Discipline on Employee Performance in South Labuhanbatu Regency Transportation Agency - Hasibuan, Syafrina Nugraheni; Nasution, Meisa Fitri (PT Aksara Indo Rajawali, 2025)
Performance in human resource research is always a reference or choice of topics with quite high intensity, so that almost all academics and universities in the world are favorites to choose this topic. The purpose of this study was to determine and analyze the effect of competence, work motivation, and work discipline on employee performance at the South Labuhanbatu Regency Transportation Agency. The number of people registered at this Agency is 67, consisting of Civil Servants and contracts with sampling using a census. The data collection technique used a questionnaire (Google Form). The data analysis tool used is path analysis with SmartPLS. The results of the hypothesis testing show that the variables of competence and work motivation in this study do not have a significant effect on employee performance at the South Labuhanbatu Regency Transportation Agency. At the same time, the work discipline variable is a variable that tends to strongly influence employee performance at the South Labuhanbatu Regency Transportation Agency.